Study on successful experiences of elementary school students in physical education classes in Japan - Masanori Kaji; Yuta Ono (Cogent Education, 2021)
This study seeks to clarify the structure and characteristics of learners’ successful experiences in elementary school physical education classes in Japan according to grade and sex. A questionnaire survey was administered to 1450 public elementary school students across Japan. An exploratory factor analysis revealed that successful experiences were composed of five factors: improvement in motor skills, victory, the success of others, the success of oneself, and strengthening of bonds. The scale for successful experiences was confirmed to possess internal consistency and some degree of validity. Furthermore, girls scored significantly higher in “the success of others” than boys did. Thus, for learners to have various successful experiences, it is necessary to master motor skills while interacting with others. Additionally, using the developed scale before and after the implementation of the study unit is expected to reveal multifaceted learning outcomes. These efforts will motivate learners to participate in physical education classes.